EFFECT OF LEMON PEEL (CITRUS LIMON) EXTRACT ADMINISTRATION ON THE MACROSCOPIC AND MICROSCOPIC CHARACTERISTIC OF WISTAR MALE RATS KIDNEYS WITH HYPERURICEMIA - Indira Pramesti Poerwanagara; Mahayu Dewi Ariani; Endang Mahati; Yora Nindita (Faculty of Medicine, Universitas Diponegoro, Semarang, Indonesia, 2025)
Background: High purine consumption can increase uric acid levels. Elevated uric acid levels can lead to complications in the kidneys, including damage and the formation of kidney stones. Lemon peel contains vitamin C, flavonoids, and citrate that can act as antioxidants and inhibitors of kidney stone formation. Objective: Investigating the effects of graded doses of lemon peel extract (Citrus limon) on the macroscopic and microscopic characteristics of kidneys in male wistar rats with hyperuricemia and comparing among control, positive control, and treatment groups. Methods: Thirty samples of experimental rats were divided into 5 groups: a control group, a positive control group, and 3 treatment groups, with each group consisting of 6 rats. The samples were administered Maggie cube broth produced by PT. Nestle Indonesia at a dose of 140 mg/200gBW for Wistar rats and potassium oxonate at a dose of 50 mg/200gBW for inducing hyperuricemia. Intervention involved oral administration of lemon fruit peel extract at doses of 17.5, 35, and 70 mg/kgBW for 14 days. Rats were terminated for kidney extraction, followed by macroscopic and microscopic readings. Differences between groups were analyzed using statistical tests. Results: No significant differences were found in the macroscopic appearance of the kidneys among the groups, characterized by smooth and even surfaces. Microscopic observations showed that kidney preparations P1, P2, and P3 had lower rates of tubular cell degeneration compared to K1, although no significant differences were found in the inflammation observed between K1 and P1, P2, and P3. Conclusion: This suggests that lemon fruit peel extract affects the rate of tubular cell degeneration in Wistar rat kidneys. However, there was no effect on the inflammation observed.